1987
DOI: 10.1128/jb.169.5.1878-1885.1987
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of signaling in bacterial chemotaxis

Abstract: Strains missing several genes required for chemotaxis toward amino acids, peptides, and certain sugars were tethered and their rotational behavior was analyzed. Null strains (called gutted) were deleted for genes that code for the transducers Tsr, Tar, Tap, and Trg and for the cytoplasmic proteins CheA, CheW, CheR, CheB, CheY, and CheZ. Motor switch components were wild type, flaAII(cheC), orflaBll(cheV). Gutted cells with wild-type motors spun exclusively counterclockwise, while those with mutant motors chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 37 publications
4
162
0
Order By: Relevance
“…However, the occurrence of this phenomenon in other two-component regulatory systems taken together with the common knowledge that extremely biased flagellar rotation per se can result in a non-chemotactic phenotype raises the question whether the extreme bias of null chemotaxis mutants may be a cause of their lack of response in chemotaxis assays. Flagellar rotation can be made less counterclockwise (CCW) biased by intracellular overproduction of the response regulator CheY (Clegg and Koshland, 1984;Wolfe et al, 1987). Here, we demonstrate that null chemotaxis mutants, made less CCW biased in this manner, exhibit a chemotactic-like response to chemoeffectors.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, the occurrence of this phenomenon in other two-component regulatory systems taken together with the common knowledge that extremely biased flagellar rotation per se can result in a non-chemotactic phenotype raises the question whether the extreme bias of null chemotaxis mutants may be a cause of their lack of response in chemotaxis assays. Flagellar rotation can be made less counterclockwise (CCW) biased by intracellular overproduction of the response regulator CheY (Clegg and Koshland, 1984;Wolfe et al, 1987). Here, we demonstrate that null chemotaxis mutants, made less CCW biased in this manner, exhibit a chemotactic-like response to chemoeffectors.…”
Section: Introductionmentioning
confidence: 74%
“…Wolfe (personal communication) found that the gutted strain HCB437 that overexpresses CheY responds to galactose by increasing CCW rotation. (c) Wolfe et al (1987) did not find a response of tethered cells of a Y þ -gutted strain to 10 ¹4 M aspartate. This finding is in agreement with our observation that the net response to aspartate at this concentration is zero (Fig.…”
Section: Earlier Observations Of Similar Phenomenamentioning
confidence: 89%
See 3 more Smart Citations